Review of insulation monitoring and fault locating devices for ungrounded low voltage network: Commercial products, patents, research and innovation - Azharudin Mukhtaruddin; Muhammad Mokhzaini Azizan; Mohd Faris Ariffin (Elsevier BV, 2026)
Indexed by WOS/Scopus/ERA